Pemberdayaan Masyarakat UMKM Sulawesi dalam Implementasi Digitalisasi UMKM - Hasnawiya Hasan; Haliah Haliah; Muhammad Alief Fahdal (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: The aim of this service is to convert the conventional UMKM into digital UMKM in order to upgrading the marketing method of UMKM so that they can operate their business efficiently as well as increase their income from this business. Method: The community service team of Hasanuddin University role is to form a digitalize marketing method for these UMKM by design a business website. The Hesamuddin University team design a business website with PHP, Java Script, CSS language using Visual Studio Code software. In addition, the community service team of Hasanuddin University also has conducted socialization and training for public and partners. Result: The result of this project is successfully launching the business website as well as expand their market nationally and increase their income gradually from this business. So that, this community service activity, has gradually transform the UMKM society particularly the partner into UMKM digital society.